Continuum diabetes care among tuberculosis patients in a rural block of Eastern Odisha - Binod K Behera; Binod K Patro; Biswanath Padhi (Wolters Kluwer Medknow Publications, 2023)
Introduction: Interaction between TB and DM shows that 10% of the TB cases globally are linked to DM. The weaker immunity of patients with chronic diseases like DM is at higher risk of progressing from latent to active TB. A large portion of DM and TB patients remain undiagnosed or get diagnosed later. TB-DM comorbidity complication appears and leads to high treatment costs and out-of-pocket expenditure. Glycemic control in TB patients can improve treatment outcomes. All TB patients diagnosed and registered under RNTCP will be referred for screening for diabetes. The present study was conducted to describe the continuum of TB-DM care among TB patients. Material and Methods: Retrospective record reviews in three randomly selected TU, which included all the patients registered during October 2017-March 2018. Results: A total of 145 patients' treatment cards were available for review and analysis. More than half, i.e., 52%, were in the 14-44 age-group. During the anti-tuberculosis treatment (ATT), 46.2% were unemployed. 15.9% of patients were not screened for DM, ten patients were known cases of DM, 11 TB patients were found to be newly diagnosed as having DM, and out of them, only two patients could be initiated with DM treatment. So, in the present study, 21 out of 145 TB patients, 14.5% had DM. Conclusions: It is evident from this study that TB patients with DM, either known case or newly diagnosed, are not receiving the proper DM care that they should receive as per the program provision.